Psychometric validation of teacher empathy scale: Measurement invariance in gender - Samavi, Abdolvahab; Hajializadeh, Kobra; Javdan, Moosa; Farshad, Mohamad Reza (Frontiers in Psychology, 2022)
Result from Wang et al. study described the development and validation of an empathy scale for teachers (EST) and suggested that the EST could be an effective tool to assess the empathy of primary, middle and high school teachers in relation to their students. This study examines the factorial structure and factorial invariance of the EST in an Iranian sample. Confirmatory factor analysis was conducted to explore dimensionality and test for measurement invariance in factor structure, factor loadings and intercepts across gender in a sample (N = 462), of Iranian high-school male and female teachers (24–55 years). The data supported the multidimensional structure in both male and female samples. Accordingly, all factor loadings were significant and scale structure confirmed like the original scale. The results indicated that the EST includes three dimensions: cognitive empathy, negative affective empathy and positive affective empathy, and the internal consistency reliability of the three subscales are satisfactory in total sample and both sexes. Furthermore, the results revealed that invariance of the measure according to gender was confirmed. In addition, as the validity evidence, the EST is positively correlated with empathic concern scale scores. The study suggests that the EST could be an effective tool to measure the empathy of high school teachers in relation to their students in Iranian sample.